Connect with knowledgeable individuals and find the best answers at IDNLearn.com. Receive prompt and accurate responses to your questions from our community of knowledgeable professionals ready to assist you at any time.

3x^2-2x(x+1)=x^2+x-6

Sagot :

Answer:

x = 2

Step-by-step explanation:

3x² - 2x(x + 1) = x² + x - 6 ← distribute and simplify left side

3x² - 2x² - 2x = x² + x - 6

x² - 2x = x² + x - 6 ( subtract x² + x from both sides )

- 3x = - 6 ( divide both sides by - 3 )

x = 2

Step-by-step explanation:

3x^2-2x(x+1) = x^2 +x-6

3x^2−2x(+1)=x^2+xx−6

3x^2−2x^2−2x=x^2+x−6

3x^2−2x^2-2x=x^2+x−6

1x^2-2x=x^2+x-6

1x^2−2x=x^2+x−6

x^2−2x=x^2+−6

solution:

x=2